Pineocytoma Mimicking a Pineal Cyst on Imaging: True Diagnostic Dilemma or a Case of Incomplete Imaging? - Fakhran, S.; Escott, E.J. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Pineocytomas have been described as well-circumscribed, homogeneously enhancing masses. However, there is considerable variability in this appearance, and certain pineocytomas may have a predominantly cystic appearance on imaging. This has led some to suggest that differentiation between pineocytomas and pineal cysts may not be possible. We have attempted to determine if cystic pineocytomas could be found in a series of these tumors evaluated by CT and MR imaging.MATERIALS AND METHODS: We searched the radiology literature as well as the medical records from our own institution for pathologically proved pineocytomas with available preoperative imaging or imaging reports, with specific focus on whether postcontrast MR imaging was included. In cases in which images were available, they were evaluated by a Certificate of Added Qualification (CAQ)-certified neuroradiologist and a radiology resident, who attempted to determine if the pineocytomas had any MR imaging characteristics of typical pineal cysts. To be considered a typical pineal cyst, an area of signal-intensity abnormality must be centered on the pineal recess, demonstrating internal homogeneity on T2-weighted imaging, following CSF signal intensity on T1- and T2-weighted images, without any marginal lobularity or nodular contrast enhancement and a wall thickness of <2 mm. In cases in which imaging was not available, radiology reports and/or descriptions provided in the radiology literature were reviewed by a CAQ-certified neuroradiologist. For any lesion described as cystic, we again attempted to elucidate the exact extent of imaging that was performed, note specific lesion characteristics, and determine if the lesion met the criteria described previously. Finally, for tumors in which image size was provided, the mean value of maximal tumor dimension, SD, median, and range were calculated.RESULTS: Forty-four pathologically proved cases of pineocytomas from the radiology literature, as well as 8 pathologically proved cases of pineocytomas from our institution with available imaging studies and/or reports, were reviewed. Of these, 23 were solid masses, and 7 were partially solid and cystic, whereas 14 tumors could not be completely characterized due to incomplete imaging evaluation. Eight were primarily cystic; however, none of these could be confidently characterized as meeting the criteria for a typical cyst.CONCLUSION: In our analysis, no truly cystic pineocytomas were identified.